The Tibial Plateau fracture—Current incidence and treatment in Germany - Julia Elisabeth Lenz; Lorenz Huber; Josina Straub; Wolf Bäumler; Volker Alt; Johannes Weber (PLoS ONE, 2025)
Purpose This study aims to analyze the epidemiology, incidence, and treatment of tibial plateau fractures in Germany from 2019 to 2022. The focus is on understanding demographic trends, clinical presentations, and surgical management strategies for this severe injury. Methods A retrospective cohort study was conducted using data from the German Institute for the Hospital Remuneration System (InEK) from 2019 to 2022. Cases were identified using the International Classification of Diseases 10th Revision (ICD-10) codes related to tibial plateau fractures, and documented surgical procedures were categorized using OPS codes. The Patient Clinical Complexity Level (PCCL) was used to assess the severity of cases. Results A total of 79,158 cases of tibial plateau fractures were recorded during the study period, with an incidence of 22.4–25.3 per 100,000 inhabitants. Women were more frequently affected, accounting for 61.5% ± 1.1% of cases annually. The average hospital stay was 9.2 ± 0.1 days, and 76.5% ± 0.5% of patients were categorized at PCCL 0. Most fractures were multifragmentary 68.8% ± 1.3%, and the predominant documented treatment method was open reduction and internal fixation with plate osteosynthesis 63.5% ± 2.8%. 23.6% ± 2.2% of cases required bone grafting, with a preference for allografts. Conclusions Tibial plateau fractures represent a significant and stable burden in Germany, with an incidence ranging from 22.4 to 25.3 per 100,000 inhabitants. Women accounted for 61.5% ± 1.1% of cases, highlighting a gender-related predisposition. The mean hospital stay remained stable at 9.2 ± 0.1 days. The study underscores the need for tailored treatment strategies and highlights the importance of preventive measures, particularly for the elderly population, in order to reduce the incidence of these fractures. Future research should focus on improving surgical techniques and postoperative care to enhance patient outcomes and potentially reduce hospital stay durations.